Increasing Tax Payer Compliance Land and Building Taxes with Awareness and Socialization as Moderating Variables - Sanulika, Aris (EAJ (Economic and Accounting Journal), 2023)
This study aims to determine the increase in land and building taxpayer compliance with awareness and compliance as moderating variables. This research was conducted on land and building taxpayers in Cengkareng District, with a total population of 97,191 land and building taxpayers. The sampling technique was simple random sampling using the Slovin formula with a significant level of 10% so that a research sample of 100 correspondents was obtained. The data analysis method in this study is moderated regression analysis, with the results showing that awareness has a positive effect on land and building taxpayer compliance, with the socialization variable as a moderator able to strengthen the level of influence of awareness on land and building taxpayer compliance.